PENGARUH PENGETAHUAN KEUANGAN TERHADAP PERILAKU KEUANGAN MAHASISWA PENDIDIKAN EKONOMI ANGKATAN 2016 FKIP UNTAN - Miranda Ayu Ningsih; Bambang Genjik Sumartono; F.Y. Khosmas (Universitas Tanjungpura, 2021)
Abstract This study aims to find out the influence of financial knowledge on student financial behavior. Research method using quantitative approach with descriptive method. The population in this study was students of Economic Education Class of 2016 FKIP Untan which amounted to 133 students and sampling techniques using Purposive Sampling with a total of 57 people from students who are residents in boarding schools/ dormitories. Data collection techniques are questionnaires and documentation. The results of this study showed: (1) Financial knowledge of economic education students class of 2016 FKIP Untan has a percentage of 61.4% with a very high category. (2) The financial behavior of economic education students of the Class of 2016 FKIP Untan has a percentage of 38.6% in the Good category. (3) Financial knowledge has a positive and significant effect on financial behavior by 42.2%. It is based on the value of t calculate > t table (6,341 > 2,004) and the significance value of 0.000 < 0.05 , then Ha is accepted. The conclusion of this research is that there is an influence of financial knowledge on the financial behavior of students of Economic Education Class of 2016 FKIP Untan. Keywords: Financial Knowledge, Financial Behavior, Students